Protein Digestibility, Calcium and Phosphorus Retention in Rations using Gamal Leaf Flour and Cekuti Leaf Flour for Turkey Grower Poultry - Fadlu Muhammad Amrulloh; Istna Mangisah; Bambang Sukamto (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2019)
This study aimed to determine the digestibility of crude protein, calcium and phosphorus retention in rations using gamal leaf and cekuti leaf flour on grower turkey poults. Animals used were 8 weeks old turkey, totaling 100 unsex. The study used a randomized block design (RBD) using 5 treatments and 4 groups. Grouping was based on body weights; group 1 has a weight of 725 - 849 grams, group 2 has a weight of 850 - 974 grams, group 3 has a weight of 975 - 1099 grams, group 4 has a weight of 1100 - 1224 grams, each group consisting of 25 turkeys. The treatments given include T0 = without any gamal and cekuti given, TI = giving rations with 5% gamal, T2 = giving rations with 10% gamal, T3 = giving ration with 5% of cekuti and T4 = givingration with 10% of cekuti. The data obtained were carried out by the F test and Duncan's multiple range with a level of 5%. The results showed that the use of gamal leaf flour and scruff on the ration for grower turkey had a significant effect (P˂0.05) on crude protein digestibility, calcium and phosphorus retention and in grower turkey. The conclusion is that as much of 5% gamal leaf flour can be used in turkey rations.